Ethical Capital; Religious Education and Graduate Employability - Choirunni’mati Akmal, Rasya; Daryono (Inovasi Analisis Data, 2025)
Purpose: The aim of the present study is to explore the role of ethical capital in graduate employability, as measured by the economic worth attributed to character, as it is understood within the context of religious education, through the framework of university training.Method: The present study employs a quantitative cross-sectional design, with a sample of 312 undergraduate students from public and private universities in Semarang, Indonesia. Hierarchical multiple regression analyses were performed in SPSS 28.Findings: The internalization of religious values, the quality of religious pedagogy, and the institutional religious climate have been identified as significant positive predictors of professional character formation. Furthermore, the students' self-perception of being prepared for a career structure is influenced by these associations even more powerfully, suggesting that if students understand that the market values virtue, they are far more likely to turn their religious education into professional character.Novelty: The present study proposes a novel conceptualization of